Impact of The Pandemic on The Mental Health Of Journalists in Blitar City During PPKM - Anita Reta Kusumawijayanti Muslihin (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
Abstract The threat of the corona virus makes journalists have to work extra. They have to adapt this situation. Media institutions are also very much needed to educate and provide awareness for the public in the Covid-19 pandemic era. However, pandemic era has made the work of journalists more dangeraous and full of risk. Journalists has high mobility and dynamics so they often feel anxious at work because they meet many people. Based on the these facts, the researcher conducted a study about impact of the Covid-19 pandemic on the mental health of journalists in Blitar city during the Enforcement of Community Activity Restrictions (PPKM). This research uses a qualitative approach. The researcher collects data from journalists during the news production process, which is devided into pre-production, production, and post-production. They cover the news in Blitar city and have been exposed to Covid. The researchers also wanted to learn about journalists' efforts to maintain mental health during the pandemic. From the data analysis, it can be concluded that Covid-19 has had an impact on various sectors including journalists and media industry. Pandemic has changed the pattern of interaction and adaptation of technology rapidly. During pandemic the duty of a journalists is very difficult and challenging. Journalists often ignore mental disorders such as anxiety, fear, working extra hours, and more vulnerable to catching covid-19. Keywords : Impact of Pandemic , Journalists, Mental Health, PPKM,